1999
DOI: 10.1080/09638199900000004
|View full text |Cite
|
Sign up to set email alerts
|

Exports, export composition and growth

Abstract: The relationship between trade and growth has been central to development economics with particular emphasis on the export-growth dynamic. The current paper is in the tradition of this literature but develops two new strands. First, it examines the exports-growth link in a dynamic fashion, providing a more rigorous approach than has been attempted previously. Second it explores the role of export composition in determining growth performance. By constructing a panel of 69 countries and using the dynamic model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 16 publications
3
56
0
4
Order By: Relevance
“…In his empirical analysis, he estimated neoclassical models where growth of GDP was a function growth of capital and labor and ELG models that also included growth of aggregate real exports; the ELG models explained more of the growth than the neoclassical models. Although Feder did not include it in his models, other authors (e.g., Barro 1991;Sachs and Warner 1995;Greenaway et al 1999) estimating GDP growth have argued that countries with lower initial levels of income per capita tend to growth faster in the short run, thus tending to converge to the GDP per capita levels of higher income countries. Some more recent ELG studies have expanded on the role of exports in explaining growth of GDP.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In his empirical analysis, he estimated neoclassical models where growth of GDP was a function growth of capital and labor and ELG models that also included growth of aggregate real exports; the ELG models explained more of the growth than the neoclassical models. Although Feder did not include it in his models, other authors (e.g., Barro 1991;Sachs and Warner 1995;Greenaway et al 1999) estimating GDP growth have argued that countries with lower initial levels of income per capita tend to growth faster in the short run, thus tending to converge to the GDP per capita levels of higher income countries. Some more recent ELG studies have expanded on the role of exports in explaining growth of GDP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since we were not able to find surveys of these studies other than Mookerjee, we cite a few examples. Greenaway et al (1999) estimated growth for all exports and then for different categories of exports; they found exports of fuels, metals and textiles had more effect on growth than food or other primary products. Al-Marhubi (2000) found that share of manufactured goods and more diverse exports increased growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it can be argued that while export specialization may be important for efficiency and growth, it does matter what the nature of specialization is (Naude, bosker & Matthee, 2010). For instance, export specialization is positively related to growth, and the strength of the link varies with each sector of specialization (Greenaway, Morgan & Wright, 1999). Also, export specialization in goods with a high technological content has been found to be important for long-term growth (crespo-cuaresma & Wörz, 2005), and in the presence of knowledge-spillovers, the mix of exported products may have important consequences for growth (Hausmann, Hwang & Rodrik, 2009).…”
Section: The Role Of Trade Diversificationmentioning
confidence: 99%
“…The degree of openness is deemed crucial for economic growth. Studies examine the relationship between different proxies for globalization and economic growth find a significant and positive relationship connecting these variables in the recipient country (Dollar & Kraay, 2001;Greenaway et al, 1999). Borensztein et al (1998) demonstrate a positive effect of foreign direct investment on the level of human capital availability.…”
Section: Economic Globalization (Kaop)mentioning
confidence: 99%